PENGASUHAN : SERTA PENGASUHAN MENURUT RAGAM SOSIAL BUDAYA - Miranti, Windi; Balqista, Azah Nadya; Maharani, Esi; Triagustriani, Jeni; Putri, Yecha Febrieanitha (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
This article discusses the method of measuring and assessing parenting and parenting according to socio-cultural diversity. The purpose of this article is to find out how the methods of measuring and assessing in parenting are, as well as knowing the various kinds of parenting in various socio-cultural contexts. Parenting itself can be interpreted as a series of activities carried out by parents to carry out their role as parents. Measurement is defined as an action to identify the size of the symptoms. Assessment is a process of collecting data to determine to what extent, and in what ways, how educational goals have been achieved, what and how they have not been achieved and what are the causes and follow-up actions. Parenting according to socio-cultural diversity, as we know that social and cultural greatly influences every aspect of children's education as human beings who grow through beliefs and practices designed to promote a healthy adaptation. Cultural values are also used to build links between the present and the past.